THE EFFECT OF STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) AND LEARNING MOTIVATION TOWARD THE STUDENTSâ READING COMPETENCE OF THE EIGHTH YEAR STUDENTS OF SMP N 3 UBUD IN THE ACADEMIC YEAR 2012/2013 - Pt, Jony Anto,; N.Y, Padmadewi,; A., J., N, Putra, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study was an experimental research which aimed at identifying the effect of implementation of Student Team Achievement Division (STAD) and learning motivation toward studentsâ reading competence. This research used 2x2 factorial designs. The data collected through test and analyzed by using statistical Two-Way Anova and Tukey Test. The population was 4 classes (197 students) of grade VIII SMP Negeri 3 UBUD in academic year 2012/2013 in which 2 classes were chosen as the sample of the study. The chosen of two classes as a sample used intact Random Sampling. The results of the research were first, there was a significant different effect between the students taught by using STAD method and conventional method. Second, there was an effect of learning motivation toward student reading competence. Third, there was a significant interactional effect between implementation of studentâs team achievement division (STAD) and Learning motivation toward students reading competence. Forth, there was a significant different effect between the students having high motivation taught by using student team achievement division (STAD) and conventional method. Fifth, there was a significant different effect between the student having low motivation taught by using student team achievement division (STAD) and conventional method. Keywords: Reading, Learning Motivation, High Motivation, Low Motivation, STAD Method, Conventional Method.